Giant Perpendicular Magnetic Anisotropy in Mo‐Based Double‐Interface Free Layer Structure for Advanced Magnetic Tunnel Junctions. (15th July 2020) - Cheng, Houyi; Chen, Jingle; Peng, Shouzhong; Zhang, Boyu; Wang, Zilu; Zhu, Daoqian; Shi, Kewen; Eimer, Sylvain; Wang, Xinran; Guo, Zongxia; Xu, Yong; Xiong, Danrong; et al.
Abstract: A strong perpendicular magnetic anisotropy (PMA) and a high thermal stability are essential for long‐term stable storage of data in PMA‐based magnetic tunnel junctions (p‐MTJs). This work investigates the magnetic anisotropy of the MgO/CoFeB/X/CoFeB/MgO double‐interface free layer stacks, where X represents the spacer material. After annealing at 350 °C for an hour, interfacial magnetic anisotropy ( K i ) as high as 4.06 mJ m −2 is obtained in the MgO/CoFeB/Mo (0.4 nm)/CoFeB/MgO stacks, much higher than those for Ta‐ and W‐based films. Experimental and first‐principle calculation results demonstrate that bulk PMA plays a great role in the Mo‐based structure, which is often negligible in Ta‐ and W‐based structures. Moreover, a strong PMA is achieved after annealing at 500 °C, which is attributed to the weak interdiffusion and good uniformity as shown in high‐resolution transmission electron microscopy and energy‐dispersive X‐ray spectroscopy results. These findings help to understand the origin of strong PMA in Mo‐based structures and show the promising prospect of using this structure for high‐packing‐density p‐MTJs and other spintronic device applications down to 10 nm scale. Abstract : It is demonstrated that a Mo‐based double‐interface free layer structure exhibits much stronger perpendicular magnetic anisotropy (4.06 mJ m −2 ) than Ta‐ and W‐based counterparts. Strong perpendicular magnetic anisotropy (2.93 mJ m −2 ) can still be realized after annealing at 500 °C. Furthermore, theoretical and experimental results show that the bulk magnetic anisotropy is critical in this structure.